Implementasi Metode Al Miftah dalam Meningkatkan Kemampuan Membaca Kitab Kuning dengan Menggunakan Pendekatan Behavioristik di Pondok Pesantren Raudlatul Ulum II - Vivi Lailatul Unzi; Pramesti Retno Suryaningtyas (Jurnal Riset Rumpun Agama dan Filsafat, 2026)
This study aims to examine the effectiveness of implementing the Al Miftah method with a behavioristic approach in improving the ability of students at the Raudlatul Ulum II Islamic Boarding School to read classical Islamic texts. This method provides stimuli in the form of repetitive exercises and positive reinforcement that actively motivate students to learn nahwu and sharaf rules, the main foundations in learning classical Arabic texts. The results of observations and interviews show significant changes in the students' learning behavior; from being passive to being more active, motivated, and able to understand the learning material better. The use of innovative media such as nadhom songs strengthens the memorization of Arabic language rules in a rhythmic and enjoyable way. The role of teachers as facilitators and evaluators is also very important in guiding and motivating students individually. Evaluation of students' abilities through classical Islamic texts reading tests shows that this method is effective in improving reading performance and understanding of classical Islamic texts. Some limitations, such as limited learning time and the number of certified teachers, are concerns for future development.